Examining the Impact of Promotional Strategies and Digital Marketing on Student Enrollment Decisions in Tutoring Centers: A Case Study of Medan - Megawaty Megawaty; Dwi Fany Fransiska Dewi Butar Butar; Hafni Cholida Nasution (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research investigates the influence of promotional strategies and digital marketing on students' decision-making processes when selecting tutoring services at Course Centre Medan, Indonesia. The study addresses the declining student enrollment attributed to ineffective promotional activities and limited digital marketing utilization. Materials and Methods: A quantitative research design was employed with 50 students as respondents using saturated sampling technique. Data were collected through structured questionnaires measuring promotion (8 items), digital marketing (10 items), and decision-making (8 items) using a 5-point Likert scale. Multiple linear regression analysis was conducted using SPSS version 22 to examine the relationships between variables. Results: The multiple linear regression analysis yielded the equation Y = 9.272 + 0.306X₁ + 0.352X₂ + e, indicating positive relationships. Partial testing revealed that promotion significantly influences student decision-making (t = 3.389 > 2.011, p = 0.001), as does digital marketing (t = 3.353 > 2.011, p = 0.002). Simultaneous testing demonstrated that both variables collectively impact decision-making (F = 12.309 > 3.19, p < 0.001). The coefficient of determination (R²) was 0.316, indicating that 31.6% of variance in student decision-making is explained by promotion and digital marketing. Conclusions: Both promotion and digital marketing significantly influence students' decisions in choosing tutoring services. Digital marketing demonstrates a slightly stronger effect (β = 0.397) compared to promotion (β = 0.402). Educational institutions should prioritize integrated marketing strategies combining traditional promotional methods with digital platforms to enhance student recruitment and enrollment.